Future proof : how to build resilience in an uncertain world - Coaffee, Jon (Yale University Press, 2019)
Catastrophic events such as 9/11, Hurricane Katrina, and the Tohoku "Triple Disaster" of earthquake, tsunami, and nuclear meltdown that hit the eastern seaboard of Japan in 2012 are seen as surprises that have a low probability of occurring but have a debilitating impact when they do. In this eye-opening journey through modern and ancient risk management practices, Jon Coaffee explains why we need to find a new way to navigate the deeply uncertain world that we live in. Examining how governments have responded to terrorist threats, climate change, and natural disasters, Coaffee shows how and why these measures have proven inadequate and what should be done to make us more resilient. While conventional approaches have focused on planning and preparing for disruptions and enhanced our ability to "bounce back," our focus should be on anticipating future challenges and enhancing our capacity to adapt to new threats